Flora of Khandagiri and Udayagiri: An Urban Heritage of Odisha - Das, Mohini Kanti; Das, Prabhat Kumar; Kumar, Sanjeet; Singh, Nihar Ranjan (Indian Forester, 2020)
The Khandagiri and Udayagiri hills are situated in the heart of temple city Bhubaneswar with about 411 species of plants. The vegetation here more or less conforms to tropical low mixed and semi evergreen forest and dry evergreen forest type vegetation, characteristic of sandstone hills that are similar to Chandaka-Dampada-Nandanakanan range. Additionally, the area is home to over 100 species of medicinal plants, wild edible fruit plants and several botanically interesting species. Gardenia latifolia, Memecylon umbellatum, Pterospermum xylocarpum, Alphonsea madraspatana, Desmodium alysicarpoides, Syzygium cerasoides, Canthium dicoccum, Manilkara hexandra, Sarcostemma acidum, Croton caudatus are some of the characteristic plants found in this hill. The paper highlights the needs of conservation of this unique threatened habitat which might help in its long-term protection and conservation.